Trade negotiations when market access matters - Mrazova, M (University of Oxford, 2009)
This paper analyses GATT/WTO trade negotiations in an oligopolistic multi-country setting and identifies a new rationale for trade agreements. When set unilaterally, tariffs are inefficiently high, both for familiar terms-of-trade reasons, but also to restrict market access of foreign firms. Trade agreements neutralise both the terms-of-trade and the market-access externalities and help countries reach efficient tariff levels. The paper further studies various kinds of asymmetries in trade negotiations. It is shown that the multilateral negotiations system can sustain only a certain level of free-riding which suggests why multilateralism was successful in the past, but is currently stalling.